A Critique and Review on the Book Scythians Warriors of Ancient Siberia - Shahin Aryamanesh; Sorour Khorashadi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The Scythians tribes were one of the nomadic tribes inhabiting large areas in the central Eurasian steppes from about the 9th century BC up until the 4th century AD. These tribes moved into parts of present-day Iran after many displacements in the first millennium BC. These tribes have played important role in central Eurasian steppes and in Persian and part of India. What scholars know about the Scythians tribes based on the writings of Herodotus. These people have played an important role in Persian and Indian epics, as well as in various historical periods of Iran, such as the Iron Age and Achaemenid and Parthian periods. Their presence in Iran has been illustrated by at least the name of one of the Iranian cities, Sakestan or Sistan, which is the name of these people. Few archaeological findings in Iran have been attributed to Scythians. However, in recent years, new burial grounds have been found which shed new light on the Scythian’s presence in Persia and central Eurasian that appears to confirm the writing of historians. In recent years many articles and books have been published about Scythians based on archaeological findings. Recently a new book has been published entitled Scythians Warriors of Ancient Siberia. This paper critically reviews this book edited by St. John Simpson and Svetlana Pankova.